Difficulties Students face in Sight Translation Exams: A Case Study at the University of Sulaimani- Department of Translation (Raparin Journal of Humanities (RJH), 2021)
The method of orally reproducing a written text in a target language is called sight translation (STr). This method is used as a bridge between translation and interpreting which is now considered as its mode of interpreting. Sight translation is two-toned because it requires both reading and speaking; therefore, students face difficulties and challenges while performing the task.The purpose of this study is to highlight the problems students face before taking an exam in sight translation and during the exam. To conduct the study, depending on Likert-scaled questions, fifteen senior students participate in a two-part quantitative questionnaire. The first part is a pre-test questionnaire in which students are asked to answer a set of questions to highlight the challenges they face before the exam. Later, the students are asked to translate a text from English into Kurdish, through which the researcher tries to evaluate the students’ translation and their abilities to overcome the problems they face in performing sight translation according to sight translation exam criteria. Soon after, the students perform the post-test questionnaire in which they give their reviews about the challenges they had during the exam. The whole questionnaire is designed to validate the results of the students in sight translation exams. This paper is helpful to understanding the students’ challenges in sight translation and helps the translation teachers to make appropriate pedagogical decisions to ease the challenges students face during sight translation.